2017
DOI: 10.3386/w23461
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Accountability and Education Production: Evidence from NCLB Waivers

Abstract: In 2011, the U.S. Department of Education granted states the opportunity to apply for waivers from the core requirements of No Child Left Behind (NCLB). In exchange, states implemented systems of differentiated accountability in which they identified and intervened in their lowestperforming schools ("Priority" schools) and schools with the largest achievement gaps between subgroups of students ("Focus" schools). We use administrative data from Michigan in a series of regression-discontinuity analyses to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…13 Using these measures, we do not find evidence that Focus Schools' student enrollment changed within the first two to three years after their assignment, relative to any changes that occurred at other schools close to the SPS threshold. These findings are consistent with those from research on the impacts of the school grade accountability systems in Florida (Chakrabarti, 2007;Figlio and Rouse, 2006;Chiang, 2009), New York City (Winters and Cowen, 2012), and Michigan (Hemelt and Jacob, 2017), all of which do not find evidence that changes in student composition were drivers of the patterns of school performance they found.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…13 Using these measures, we do not find evidence that Focus Schools' student enrollment changed within the first two to three years after their assignment, relative to any changes that occurred at other schools close to the SPS threshold. These findings are consistent with those from research on the impacts of the school grade accountability systems in Florida (Chakrabarti, 2007;Figlio and Rouse, 2006;Chiang, 2009), New York City (Winters and Cowen, 2012), and Michigan (Hemelt and Jacob, 2017), all of which do not find evidence that changes in student composition were drivers of the patterns of school performance they found.…”
Section: Resultssupporting
confidence: 87%
“…Michigan (Hemelt and Jacob, 2017) but differ with respect to the Focus School reforms in Kentucky (Bonilla and Dee, 2017). For Kentucky, the authors found positive impacts as a result of Focus School assignment in both math and reading for the targeted "gap group" students.…”
Section: These Null Findings Resemble Those Based On Focus and Priorimentioning
confidence: 92%
“…Given that different factors shape the decision to close a charter school compared with a traditional public school, we also exclude studies examining the effect of charter school closure on student outcomes (e.g., Carlson & Lavertu, 2016; Chingos & West, 2015). Finally, it should be noted that our definition allows for turnaround to occur in the context of school improvement efforts conducted under NCLB waivers (Bonilla & Dee, 2020; Dee & Dizon-Ross, 2019; Dougherty & Weiner, 2019; Hemelt & Jacob, 2017) as well as state takeover of low-performing schools (Schueler et al, 2017; Zimmer et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…A recent report from the U.S. Government Accountability Office found that many states did not effectively implement the waiver‐based reforms, and had difficulty monitoring districts and schools (Nowicki, ). Recent evaluations of Priority and Focus school reforms in several different states found that the efforts had no impact on student performance levels or achievement gaps (Bonilla & Dee, ; Dee & Dizon‐Ross, ; Dougherty & Weiner, ; Hemelt & Jacob, ). And the broader research on school turnaround efforts is not particularly encouraging either.…”
Section: The Futurementioning
confidence: 99%